Total methionine + cystine levels in diets for Muscovy ducks in housing - Julmar da Costa Feijó; Gilberto Batista Viana Filho; Fernanda Moura Fernandes Silva; Juliana da Costa Feijó; Francisco Alberto de Lima Chaves; João Paulo Ferreira Rufino; Frank George Guimarães Cruz (Acta Scientiarum. Animal Sciences, 2024)
The present study aimed to determine the ideal levels of total methionine + cystine for Muscovy ducks in confinement. Two hundred and forty Muscovy ducks of the creole strain were distributed in a completely randomized experimental design where the treatments consisted of six nutritional plans with different levels of total methionine + cystine, and four replicates (two with males only and two with females only), each with 10 Muscovy ducks. The nutritional plans considered the requirements in the initial, growing, and finishing stages. The birds had their performance evaluated weekly, and at 90 days of age, eight birds (four males and four females) from each treatment were slaughtered for the evaluation of carcass traits. Nutritional plan 3 provided a significant (p < 0.05) reduction in feed intake and an increase (p < 0.05) in weight gain, causing a proportional reduction (p < 0.05) in feed conversion. Levels above and below the requirements in this nutritional plan caused a significant (p < 0.05) loss in performance. Muscovy ducks fed with nutritional plan 3 also presented better (p < 0.05) carcass traits. A significant difference (p < 0.05) in carcass development was observed between males and females, with males showing better results.